6m2=m+1

Simple and best practice solution for 6m2=m+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m2=m+1 equation:



6m^2=m+1
We move all terms to the left:
6m^2-(m+1)=0
We get rid of parentheses
6m^2-m-1=0
We add all the numbers together, and all the variables
6m^2-1m-1=0
a = 6; b = -1; c = -1;
Δ = b2-4ac
Δ = -12-4·6·(-1)
Δ = 25
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{25}=5$
$m_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-1)-5}{2*6}=\frac{-4}{12} =-1/3 $
$m_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-1)+5}{2*6}=\frac{6}{12} =1/2 $

See similar equations:

| 144x-88=1 | | 8-2(x-5)=x+3 | | -7x2+6x+10=0 | | 4p+42=10p+12 | | 2x+8x-9x=0 | | (-2x-5)(x)=64 | | 2-3x=4-11x | | 2y/8=4-1/12 | | 4x+3=7-8x | | 1.5a+8.75=13.25 | | -10x-76=50-x | | y=6E-05X+0.568 | | 3x=800+x | | 6z-3=z+3 | | 3=8/(w-3) | | -0.4(x-3.8=-2 | | (5x-7)(9-x)=0 | | 2^x+4=20 | | x^2+x^2=6.4807406984 | | 3(2^x+4)=350 | | -z-5=5 | | 18-8m=-5(5m+3)-3m | | 10-2x=4x+6 | | X=2y+(y-8) | | X=2y^2-8 | | 2/3(x+1)=16 | | (5x-7)(9-x)=0= | | X=2y(y-8) | | 3=0.06x | | y/2+2=13 | | (X+5)+y=90 | | 2/3(2n-7)=-2 |

Equations solver categories